Turkey - Report on the Observance of Standards and Codes : Accounting and Auditing - World Bank (Washington, DC, 2012)
As work on the economics of information' demonstrates, enhancing the reliability and availability of financial reporting is conducive to economic growth and mitigating the risk of financial system instability. In that context, this report provides an assessment of accounting and auditing standards and practices in Turkey. It uses International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks and draws on good practices in the field of accounting and audit regulation to assess the quality of financial information and make policy recommendations. For European Union (EU) candidate countries such as Turkey, the assessment also has regard to the relevant requirements of EU law (also known as the acquis communautaire). There has been significant progress in recent years in improving the environment and framework for financial reporting in Turkey and currently further wide-scale reforms are in progress. In particular, a new draft commercial code will modernize statutory regulation of company financial reporting and will set a major challenge for the accounting and auditing professions in Turkey through the requirement to apply Turkish Accounting Standards based on IFRS and audits based in international Standards of Auditing (ISA).